Pelatihan Multi Meter dalam Rangka Mengembangkan Kemampuan Praktek Fisika Siswa SMA 3 Kota Batam - Yunesman, Yunesman; Johan, Dasman; Jarti, Nanda (PUAN INDONESIA, 2024)
SMAN3 Batam, as one of the well-known high schools in the city of Batam, has difficulty applying physics learning practices, specifically the use of measuring instruments. Where learning is still in theoretical form. Training on the use of The multimeter aims to improve understanding of the basic principles of the use of multimeters in physics practice, including how to measure voltage, current, and resistance correctly in the use of multimeters as electrical measuring instruments in everyday life, as well as strengthen the learning of electrical physics. The research method uses survey and observation methods carried out on students of class XII IPA SMAN3 Batam by providing training on the use of multi tester measuring instruments. To see the progress of practice by giving pretest and posttest questions from the training results The trainees can understand the basic principles of using a multimeter, including how to measure voltage, current, and resistance correctly. In the use of a multimeter, including the right technique for connecting the device to the power source and the object to be measured, and show the seriousness of the students following the training by showing a significant change in the pre-test and post-test scores. Training like this should be done on an ongoing basis.